1978
DOI: 10.1007/bf00422258
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion from pancreatic islets: Effect of growth hormone and related proteins

Abstract: Insulin responses to clinical grade human growth hormone (hGH), intact hGH, naturally occurring diabetogenic substance (NDS), and subtilisin cleaved forms of hGH (S1 and S3) were studied using hypophysectomized rat pancreatic islets. While clinical grade hGH (200 microgram/ml) elicited a prompt and sustained release of insulin, purified intact hGH (200 microgram/ml) did not. Naturally occurring diabetogenic substance, isolated from clinical grade hGH preparations, stimulated insulin release at 200 ng/ml. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…By contrast, when growth hormone is incubated with isolated islets in vitro for up to three hours, it has been shown that there is no direct stimulation of insulin release [4,9,10,11]. This confirms studies using pancreatic pieces or whole pancreatic peffusion [4,9,12,27], although here the acute stimulation of insulin release by GH has also been reported [13,28,29].…”
supporting
confidence: 78%
See 1 more Smart Citation
“…By contrast, when growth hormone is incubated with isolated islets in vitro for up to three hours, it has been shown that there is no direct stimulation of insulin release [4,9,10,11]. This confirms studies using pancreatic pieces or whole pancreatic peffusion [4,9,12,27], although here the acute stimulation of insulin release by GH has also been reported [13,28,29].…”
supporting
confidence: 78%
“…Furthermore, a factor closely associated with growth hormone, but not identical with it, may also stimulate insulin release in per• islets of hypophysectomised rats, while purified, intact, human GH will not [11]. In the light of these observations the question also arises as to whether or not growth hormone is being modified in the tissue culture to a more biologically active material.…”
Section: Short-term Action Of Growth Hormone On Insulin Release In Ismentioning
confidence: 99%
“…4, 5). A variety of fac tors have been demonstrated in pituitary' growth hormone preparations such as lipotropin, a human lipid-mobilizing factor (LMF), neurophysin, an insulotropin and diabetogenic substances [2,14,16,17,19,30,31]. The constituents observed in Cres cormon® on SDS electrophoresis migrated with a similar mobility to parts of the LMF 2 fraction (fig.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are reports indicating that growth hormone does not stimulate glucagon secretion [5] and that the insulin-releasing properties of growth hormone preparations arc due to a naturally occurring diabetogenic substance and to subtilisin-cleaved forms of growth hormone [19]. There are also contradictory reports whether growth hormone is a lipolytic hor mone in rats [8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation